Comparative assessment of remnant tensile properties of modified 9Cr-1Mo steel under prior low cycle fatigue and creep-fatigue interaction loading. (October 2017) - Mariappan, K.; Shankar, Vani; Sandhya, R.; Bhaduri, A.K.; Laha, K.
Highlights: Comparison of tensile properties change with prior fatigue damage under LCF/CFI. Yield strength reduction due to prior LCF or CFI loading important from design aspect. Decrease in YS value due to microstructural coarsening and oxidation. Difference in YS under LCF and CFI after 10% life fraction due to creep effects. Abstract: Progressive deterioration in the mechanical properties with increasing service period is commonly observed and hence needs to be addressed. Awareness about the rate of degradation of the properties can circumvent a lot of problems faced during service. Hence the present work aims to understand the degradation of tensile properties due to prior cyclic loading. Systematic comparative evaluation study for the evolution of tensile properties with prior fatigue loading and the deformation and damage evolution process in modified 9Cr-1Mo steel during low cycle fatigue (LCF) and creep-fatigue interaction (CFI) loadings has been carried out. For this, LCF and CFI experiments were carried out at constant strain amplitude of ±0.6%, strain rate of 3 × 10 −3  s −1 and temperature of 600 °C. Experiments interrupted after 5, 10, 30, and 50% of the total fatigue life (Nf ) under both LCF and CFI conditions were followed by monotonic loading at the same strain rate and temperature until fracture. Drastic reduction in the yield strength value due to both LCF and CFI prior fatigue loading was revealed and the extent of decrease in the YS values increased with the extent of prior fatigue damage imparted on the steel. Substantial difference in the YS evolution with prior fatigue damage under LCF and CFI conditions occurred only after 10% life fraction due to the predominance of creep recovery process. Factors such as microstructural changes due to creep alone or fatigue alone or both and surface oxidation changed the tensile properties under LCF and CFI.